2020
DOI: 10.1016/j.neo.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Somatic copy number alterations are associated with EGFR amplification and shortened survival in patients with primary glioblastoma

Abstract: Glioblastoma (GBM) is the most common malignant primary tumor of the central nervous system. With no effective therapy, the prognosis for patients is terrible poor. It is highly heterogeneous and EGFR amplification is its most frequent molecular alteration.In this light, we aimed to examine the genetic heterogeneity of GBM and to correlate it with the clinical characteristics of the patients. For that purpose, we analyzed the status of EGFR and the somatic copy number alterations (CNAs) of a set of tumor suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 52 publications
(86 reference statements)
3
36
0
Order By: Relevance
“…The point of iFISH remains the possibility of separating that intermediately amplified group, for which it is not entirely clear whether it represents a progression via the amplification status or a separate path for tumor progression in GB. In any case, MLPA proves to be an easy and fast technique, with the additional advantage of being able to determine mutant variants such it is EGFRvIII, in agreement with previous works [21,24,31,35].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The point of iFISH remains the possibility of separating that intermediately amplified group, for which it is not entirely clear whether it represents a progression via the amplification status or a separate path for tumor progression in GB. In any case, MLPA proves to be an easy and fast technique, with the additional advantage of being able to determine mutant variants such it is EGFRvIII, in agreement with previous works [21,24,31,35].…”
Section: Discussionsupporting
confidence: 88%
“…The use of iFISH to precisely determine the EGFR amplification status is the current gold-standard in GB [19,40]. Previous works of our and others groups, demonstrated that this method allows the detection of intermediate levels of amplification [19,24]. Lassman and his colleagues deepened the potential of different new techniques in comparison to iFISH with positive results [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In secondary GBM, mutations occur more commonly in the isocitrate dehydrogenase 1 or 2 and TP53 genes (5,6). In ~80% of GBMs, there are also changes in tyrosine kinase activity transmembrane receptor signaling pathways, the p53 pathway (TP53/mouse double minute 2 homolog/p14ARF), the phosphorylated retinoblastoma (RB) pathway [RB1/cyclin-dependant kinase (CDK) inhibitor 2A/CDK4] and the telomerase reverse transcriptase promoter region (pTERT) (7,8). The high variation in the genes involved in GBM is an important reason for the poor efficacy of chemotherapy drugs.…”
Section: Introductionmentioning
confidence: 99%